2015
DOI: 10.2174/1874364101509010172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Keratoconus Among a Palestinian Tertiary Student Population

Abstract: Purpose:To screen for keratoconus and potential associated risk factors in a tertiary student population sample.Population and Methods:This cross sectional study included 1234 students attending An-Najah National University (Nablus, West Bank, Palestine), that were randomly selected from a total of 20,000 university students. 634 (51.3%) student participants responded by completing a self-administered questionnaire and were assessed by means of corneal topography. Following initial evaluation, participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…In this cross sectional study, the prevalence of KC was 1.7% .This prevalence is consistent with the results reported in other middle-eastern countries (Shehadeh et al, 2015;Brlin et al, 2012;Millodot et al, 2011;Waked et al, 2012) where a much higher prevalence of KC is demonstrated in comparison to other regions of the world (Nielsen et al, 2007;Owens et al, 2003;Tanabe et al, 1985).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this cross sectional study, the prevalence of KC was 1.7% .This prevalence is consistent with the results reported in other middle-eastern countries (Shehadeh et al, 2015;Brlin et al, 2012;Millodot et al, 2011;Waked et al, 2012) where a much higher prevalence of KC is demonstrated in comparison to other regions of the world (Nielsen et al, 2007;Owens et al, 2003;Tanabe et al, 1985).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence in our study was comparable to the study among Palestinian tertiary students (1.5%) (Shehadeh et al, 2015) where they used simplified nomenclature for describing keratoconus among Published by SCHOLINK INC. similar age group participants (Brlin et al, 2012) but lower among Arab students in Israel where the prevalence was 3.1% as they used a simplified criteria of four topographic indices to diagnose manifest KC (Millodot et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…4 Prevalence of KC is higher in the Middle East than in other areas, as proved by literature. 9,10,[14][15][16][17] This might be due to the high incidence of chronic allergies and spring catarrh. 17 In our study, VKH was reported in 35% of cases with subclinical KC, which is comparable to the value obtained by Omar & I.A.N who reported a 37.5% prevalence of VKC in KC eyes in Egyptian children with myopia.…”
Section: Dovepressmentioning
confidence: 99%
“…Also, we divided cases into two age groups in order to highlight the higher prevalence rate of the disease among older age groups, as we report a higher percentage (8.2%) of subclinical KC among the older age group (12)(13)(14)(15)(16)(17)(18) years as compared to (1.4%) in the younger age group. A result was consistent with Awwad et al study that reported an increased prevalence of KC among increasing age groups of pediatric first-degree relatives of KC patients.…”
Section: Dovepressmentioning
confidence: 99%
“…Based on the literature as well as medical and ophthalmological expertise, it is noticed that KC is a major and common eye disease among the Palestinian population compared with other countries. This might be due to genetic and environmental risk factors, such as sun exposure (ultraviolet exposure) and nicotine [ 9 ]. Another factor associated with an increase in the risk of KC is consanguinity [ 10 ], which is prevalent in our country.…”
Section: Introductionmentioning
confidence: 99%